EFEKTIVITAS PERBANDINGAN ANTARA MINUMAN ALOE VERA DAN TEMULAWAK TERHADAP PENURUNAN INTENSITAS NYERI DISMENORE PRIMER PADA SISWA NURUL HAQ BALARAJA - Solihati; Hikmah, Agnia Nurul; Imanuddin, Bayu (Jurnal Nusantara Mandani, 2023)
ABSTRACT Background: Dysmenorrhea is a type of pain accompanied by symptoms such as lower abdominal cramps and other discomfort before and/or during menstruation. Therapy that can reduce Dysmenorrhea is pharmacological therapy by administering analgetic, non pharmacological drugs used herbal remedies such as aloe vera drinks and temulawak. The purpose of the study was to know the effectiveness of the comparison between aloe vera drink and temulawak to the decrease in the intensity of primary dismenore in MTS student Nurul Haq Balaraja. Subjects and methods: Quantitative research methodology, with research design with one group pretest-posttest design. With 30 respondents with aloe vera beverage group of 15 respondents and a group of temulawak drinks 15 respondents sempel technique using incidental is a sample determination technique based on coincidence. Results: The conclusion of the results of the study of all 30 respondents based on mann-whitney statistical test results with a statistical value of P value of 0.182≤0.05 then there is a meaningful comparison between the aloe vera group and the temulawak group so that it can be claimed that Ha was accepted and Ho was rejected. This means there is a 17.53 ratio of the effectiveness of aloe vera. Conclusion: From the results that Aloe vera drinks are more effective than temulawak drinks to decrease intensity of primary Dysmenorrhea. Keywords: Aloe vera, Temulawak, Dysmenorrhea